Analisis Penyerapan Bahasa Asing (Inggris) terhadap Bahasa Indonesia: Dampak pada Kosakata dan Pembentukan Kata Baru di Kalangan Mahasiswa - Monika Grachia Mirahel Andale; Yohana Anggilina Loru; Veronika Dasi Ta’a; Kristina Safira Ndaro; Maria Alusia Yufri Dala; Katharina Woli Namang (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Language is the primary means of communication in human life. The absorption of English into Indonesian among university students is an increasingly prominent phenomenon with the development of globalization and digital technology. This study aims to analyze the impact of this absorption on the emergence of new words or terms used by students in academic contexts and everyday communication. The research method used is descriptive qualitative. This approach was chosen because this study aims to describe and analyze linguistic phenomena and their impact on the Indonesian language. The results of the analysis show that the absorption of English has given rise to various new terms that are practical, concise, and contextual, such as deadline, submit, healing, burnout, as well as mixed forms with Indonesian affixes such as nge-print and di-upload. These terms facilitate communication and enrich students' linguistic expression. However, on the other hand, the use of these new terms has the potential to displace the use of standard Indonesian equivalents. Thus, the absorption of English has a dual impact: enriching vocabulary through the formation of new terms while also requiring a wise attitude to maintain the existence of the Indonesian language.